Expert assessments of modern political elites: elites in the context of the information society (Journal of Philosophy Culture and Political Science, 2019)
The challenges that the modern world is facing at the beginning of the 21st century primarily affect the quality of political elites and their leaders. The current elites are experiencing a serious period of breaking up the old canons and the rules of their professional activities, their competencies tested in practice are crumbling over the years, ideological principles and dogmas fall into disrepair.Nowadays, the political world is once again undergoing a test of strength. It again reveals serious system calls and threats, the solution of which in the first place falls on the shoulders of the governments of countries that consider themselves world leaders.At all times, all the elites tried to understand the laws that make them so and not otherwise function and subordinate their will, the will of these objective rules. Elitology is precisely what systematically investigates these objective laws and rationalizes them in an accessible form. This paper analyzes the expert assessment of the professional qualities of modern political elites, presents their own opinions about themselves and their colleagues, identifies the codes and meanings of their professional activities.Key words: elites, information society, crisis, challenges and threats, fakes, globalism, professional competence, memoirs, ideologies.